TAHAPAN DAN PROSES PENDIDIKAN PELATIHAN PADA BALAI REHABILITASI VOKASIONAL BAGI PENYANDANG DISABILITAS - Mursalin, Farhan; Machdum, Sari Viciawati (Jurnal Pembangunan Manusia, 2020)
Competition in the world of work that is getting tougher requires everyone to have good abilities in a certain field, especially in the era of the Asian economic community like now, competition with workers from other countries is inevitable. To answer this challenge, the government through the Ministry of Social Affairs established a Rehabilitation Center which is focused on providing skills training for persons with disabilities. The training conducted specifically for preparing persons with disabilities for the world of work by providing training and social guidance. However, in its implementation, there are various obstacles so that organizations need innovation. These obstacles occur because of limited human resources. That makes the implementation of the role of social workers and instructors to develop and become an important concern. This research examines the stages and processes in service programs at the rehabilitation center. The research approach is qualitative. While the technique of reading interview and observation data, as well as study documentation. The number of informants was 14 people, namely informants from instructors, social workers, and BBRVBD students. This study found that the service stages at BBRVBD were run linearly. However, based on the process, there are various security that cannot be avoided. Constraints occur because of various limitations that come from internal BBRVBD and from organizational organizations. Constraints that occur indirectly have implications for the process at the resocialization stage